Optimum dietary concentration of sulfur amino acids using L-methionine in the initial feed of Muscovy ducks (Cairina moschata Linnaeus, 1758) - Pujada A., Hilario (2023)
This study evaluated the effect of supplementing increasing levels of L-methionine (L-Met) in the diet for Muscovy ducks from hatch to 21 days of age. A total of 90 male Muscovy ducklings were assigned to 30 pens with 3 birds per pen. A basal diet with corn, soybean and wheat by-product was supplemented with 0, 0.08, 0.16, 0.24, 0.32 and 0.40% L-Met, obtaining 6 diets with increasing concentrations of sulfur amino acids, but constant in energy and other essential nutrients. Analysis of variance and Tukey's mean comparison test were performed. In addition, an effective dose-response model was performed to determine the optimal methionine level. Body weight and feed intake were not influenced (p>0.05) by L-Met supplementation, although a numerical trend towards greater weights was observed as supplementation increased. Feed conversion was significantly better with 0.24 and 0.32% L-Met supplementation (p<0.05), deteriorating when supplemented with 0.08% L-Met. The adequate concentration to reach the optimum body weight was determined at 0.44 and 0.72% for Met and Met+Cys, respectively. while the adequate concentration to achieve the best feed conversion efficiency was determined at 0.40 and 0.68% for Met and Met+Cis, respectively.